The Students’ Difficulty in Writing Hortatory Exposition Text At the Elevent Grade of SMA N 10 Jambi - Kartika Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The aim of this research is to describe the students ‘difficulty in writing hortatory exposition text at the eleven grade of SMA N 10 Jambi, which focus focusing on text organization (thesis, arguments, and recommendation). Design of this research is descriptive qualitative. Pre-research were done by doing interview. The data are collected by documentation (students assignment by documentation (students’ assignment made hortatory exposition text) and used quasi-statistical as the analysis method. As the result, thesis is the very most difficult part in making hortatory exposition text because twenty-one students (49%) from the overall forty-three students are unable to make thesis statement in their text. Meanwhile, the connectivity between the text organization is the most difficult in making this text because about twenty-nine (67%) from forty-three students are unable to make supporting arguments to thesis statement in their hortatory exposition text and they unable to make connectivity between recommendation and thesis statement. It means the supporting point of arguments to thesis statement is the most difficult component in arguments part and for recommendation part is in the level of recommendation connectivity with thesis statement. On the other hand most of the students proved having difficulty in text organization in making hortatory exposition text.